THE PLACE OF ABDULAZIZ MAJZUB NAMANGONIY IN THE HISTORY OF SUFISM IN CENTRAL ASIA - Aliqulova Naima Kholbekovna (International Journal of Literature and Language Studies, 2026)
This article examines the life, scholarly and educational activity, and place in the history of Sufism of Shaykh Abdulaziz Majzub Namangoniy, a nineteenth-century representative of Central Asian Sufism. It analyzes his contribution to the development of the Naqshbandiyya-Mujaddidiyya order and his founding of the mystical (irfani) current known as Majzubiylik. The article also examines, on the basis of primary sources, the poet's works, his Sufi views, his literary legacy, and the activity of the poets who followed him. Drawing on extant manuscripts and historical sources, it traces the spread of the Majzubiylik school across Turkistan and Eastern Turkistan. The findings show that Abdulaziz Majzub Namangoniy occupies an important place in the history of Central Asian Sufism and classical Uzbek literature.